The endosomal-vacuolar transport system acts as a docking platform for the Pmk1 MAP kinase signaling pathway in Magnaporthe oryzae - Wang, Qing (The New phytologist, 2025)
© 2024 The Author(s). New Phytologist © 2024 New Phytologist Foundation.